Effect of Sex and Age on Physicochemical and Technological Characteristics in the Longissimus thoracis et lumborum Muscle in Botucatu Rabbits - Villegas-Cayllahua, Erick Alonso [UNESP]; Dutra, Daniel Rodrigues [UNESP]; Dias, Ana Veronica Lino [UNESP]; Cavalcanti, Érika Nayara Freire [UNESP]; Carneiro, Nívea Maria Gomes Misson [UNESP]; Castilha, Leandro Dalcin; Borba, Hirasilva [UNESP] (MDPI, 2025)
This study aimed to assess how sex and age influence the physicochemical and technological properties of the longissimus thoracis et lumborum muscle in Botucatu rabbits. Ten samples were used from each experimental group (females and males 3 and 12 months old). Color (L*, a*, and b*), pH, water-holding capacity, cooking weight loss, shear force, percentage of collagen (soluble, insoluble, and total), myofibrillar fragmentation index, sarcomere length, cholesterol concentrations, lipid oxidation, and chemical composition were evaluated. Sex influenced (p < 0.05) the chemical composition of the meat; young females presented meat with a higher concentration of lipids and cholesterol than males of the same age; however, the opposite results were obtained with the meat of 12-month-old rabbits. Age also influenced the meat's characteristics: older rabbits had meat with more intense red and yellow colors and longer sarcomere length. In terms of chemical composition, 12-month-old rabbits had higher protein and lower soluble collagen and mineral matter compared to younger rabbits. Overall, age impacted the physicochemical properties, with older rabbits exhibiting more opaque, reddish meat, higher insoluble collagen, and lower moisture content. In addition, the influence of sex, especially on the chemical composition of meat in rabbits, must be emphasized.